"Gene" modeling approach to new glass design. (6th December 2019) - Zhang, Liyan; Xu, Yongchun; Li, Hong
Abstract: Composition‐structure‐property (C‐S‐P) approach, named as "glass structural gene modeling (GSgM), for glass database development and new glass design are detailed in this article. C‐S‐P modeling principle and modeling procedure are selectively demonstrated using two sets of phosphate glass systems with various modifications by SiO2, B2 O3, and La2 O3 . Finally, new glass design and a selective validation of the glass design are provided. The use of S‐P modeling approach, especially for single‐component studies of glass property responses in a highly nonlinear fashion, transforms one dimensional C‐P problem solving to modeling of multidimensional response space of the glass network structural groups or genes. The spectroscopically derived structural groups aided by statistical screening for significance result in better problem solving capability in the S‐P models as compared with C‐P models.